Effect of mycorrhyzation in the establishment of Pinus pseudostrobus in gullies - Gómez-Romero, Mariela; Villegas, Javier; Sáenz-Romero, Cuauhtémoc; Lindig-Cisneros, Roberto (Instituto de Ecología, A.C., 2013)
The establishment of Pinus pseudostrobus Lindl. was evaluated in three conditions of propagationand transplantation in gullies devoid of vegetation in the locality of Atécuaro, Municipality of Morelia,Michoacán. The first condition correspond to plants of known provenance, germinated and propagatedunder controlled conditions (stratified at 4 °C, germinated at 25 °C with 12 h of light and watered everyother day), with the aim of having plants without mycorrhizae and with the ectomycorrhizal fungus Pisolithustinctorius (Pers.) Coker et Couch. As a second condition, both groups where transplanted at 15 months of age with the addition of a fertilesubstrate (coconut fiber, bark and agrolite).In a nearby site, a third conditionwas a reforestation with plants of thesame species but without controlling theaforementioned variables. The resultsshow that the pine trees that were plantedin the first condition performed betterand had a higher survival than plants inthe second reforestation (third condition)(P < 000,1). The survival of inoculatedpines was 86%, in the absence of the funguswas 62% and 30% in the secondreforestation. Inoculation is a good strategyfor restoration projects in severelydegraded and eroded sites, although itincreases the costs it also increases survivaland growth.